Sistem Pengelolaan Pengarsipan Digital di Dinas Perhubungan Kota Tasikmalaya - Maulani, Hamdan; Sofyan, Verra Rosyalia Widia (POLITEKNIK LP3I, 2024)
This final assignmet entiled “Digital Filling Management System in the Transportation Department Tasikmalaya City”the research outlined in this final assignment aims to find out how the digital archiving management system is omplemented at the Tasikmalaya City Transportation Department, to find out what obstacles are faced in the digital archiving process at tha Tasikmalaya City Transportation Department. The research method used is a qualitative descriptive method which describes the results of the author’s observations while at the Tasikmalaya City Transportation Service, data colletion method using interviews, documentation and direct observation. After conducting observations and research, the author came to the conclution that the digital archiving management system ath the Tasikmalaya City Transportation Service is running very effectively.